2006
DOI: 10.1111/j.1365-2567.2006.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential polarization of immune responses by genetic cotransfer of chemokines changes the protective immunity of DNA vaccine against pseudorabies virus

Abstract: SummaryChemokines play a key role in eliciting adaptive immune responses by selectively attracting the innate cellular components to the site of antigen presentation. To evaluate the effect of the genetic adjuvant of chemokines on the adaptive immune responses induced by a plasmid DNA vaccine expressing glycorotein B (gB) of the pseudorabies virus (PrV), a PrV DNA vaccine was co-inoculated with plasmid DNA expressing certain chemokines including CCL3 (MIP-1a), CCL4 (MIP-1b), CCL5 (RANTES), CXCL8 (MIP-2), and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Furthermore, our results would indicate that statins could be utilized as immunomodulatory agents with the capacity to alter induced immune responses. It has been shown that the Th-1 and Th-2 cytokine secretory balance can be altered by statin treatment with the net effect of modulating induced immune responses against viral antigens [15], [22][24]. This could have implications for modulating the type of cellular immune response mounted in HIV-1 infected patients, with a preferential skewing towards a strengthened Th1 response and heightened CTL activity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our results would indicate that statins could be utilized as immunomodulatory agents with the capacity to alter induced immune responses. It has been shown that the Th-1 and Th-2 cytokine secretory balance can be altered by statin treatment with the net effect of modulating induced immune responses against viral antigens [15], [22][24]. This could have implications for modulating the type of cellular immune response mounted in HIV-1 infected patients, with a preferential skewing towards a strengthened Th1 response and heightened CTL activity.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported on the use of chemokines for the modulation of immune responses against viral antigens, where it was demonstrated that the coexpression of CCL3 from a DNA vaccine resulted in improved cellular and humoral immune responses against HIV proteins, with a predominant Th1 immunity (26). Interestingly, another report that compared different chemokines as genetic adjuvants for DNA-based immunization against pseudorabies virus showed a bias to Th2 after codelivery of CCL3 (47), suggesting that the predominance of either Th1 or Th2 is not strictly determined by the codelivered chemokine. One publication reports on the coexpression of CCL20 from a modified vaccinia virus Ankara-based vector and shows enhanced cellular and binding antibody responses compared to vaccination with antigen alone, which is in accordance with our results, but no data on vaccine protection after a challenge infection were shown (5).…”
Section: Discussionmentioning
confidence: 99%
“…A different approach is the coexpression of chemoattractant molecules by a genetic vaccine to recruit APCs to the site of vaccine delivery. This approach has been studied in immunotherapy of tumors (16,19,34,46) and also for vaccination against virus infections (5,13,26,47), but it has not yet been tested in a retrovirus challenge model.…”
mentioning
confidence: 99%
“…Briefly, ELISA plates were coated overnight at 4°C with an optimal dilution (0.5–1.0 μg/well) of the semi‐purified PrV antigen for sample wells and with goat anti‐swine IgG for standard wells (Bethyl Laboratories, Montgomery, TX, USA). The viral antigen used for the coating was prepared by treating the viral stock with 0.5% Triton X‐100 and then semi‐purified by centrifugation at 50 000 g (23). The plates were then washed three times with PBS‐Tween 20 (PBST), after which they were blocked with 3% nonfat‐dried milk.…”
Section: Methodsmentioning
confidence: 99%